2015
DOI: 10.1016/j.gaceta.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and temporal trends of childhood type 1 diabetes between 1975 and 2012 in Navarre (Spain)

Abstract: Since the year 2000, the incidence of type 1 diabetes among persons younger than 15 years in Navarre has been very high and has quadrupled over the last four decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The incidence among boys tends to be higher than among girls in the 10–14 years age group. This was consistent with results reported from some European regions . Because boys reach puberty later than girls, it has been suggested that physiological changes at puberty may act as triggers for diabetes .…”
Section: Discussionsupporting
confidence: 92%
“…The incidence among boys tends to be higher than among girls in the 10–14 years age group. This was consistent with results reported from some European regions . Because boys reach puberty later than girls, it has been suggested that physiological changes at puberty may act as triggers for diabetes .…”
Section: Discussionsupporting
confidence: 92%
“…29,30 US data 31 suggest an overall annualised incidence from 2001 to 2015 of about 22·9 cases per 100 000 people among those younger than 65 years; data from other regions suggest similar incidences. 32 The greatest observed increases in incidence of type 1 diabetes are among children younger than 15 years, particularly in those younger than 5 years. 33 These increases cannot be explained by genetic changes, implicating environmental or behavioural factors, or both.…”
Section: Epidemiologymentioning
confidence: 99%
“…Several studies and organizations have shown an unprecedented increase in the prevalence of diabetes worldwide (NCD-RisC 2016), including T1DM (Harjutsalo et al 2008, Patterson et al 2009, Dabelea et al 2014, Forga Llenas et al 2015, Lamb et al 2015, and the estimated number of adults with diabetes has soared to over 380 million (> 8 % world adult population, > 12% in USA) (Menke et al 2015), with a mean estimation of over 37 % with pre-diabetes and over 45 % undiagnosed according to current diagnostic criteria (Schmidt et al 2011, Federation 2015, Mechanick 2015, Menke 2015. The prevalence of T2DM in younger individuals has also increased worldwide (Holden et al 2013, Menke et al 2015, creating a new class of patients comprising children (Lustig et al 2016), adolescents and young adults (Weiss et al 2013, Song 2016.…”
Section: Definitionmentioning
confidence: 99%